ENHANCING TRANSLATION COMPETENCE IN PROSPECTIVE FOREIGN LANGUAGE TEACHERS: A FUNCTIONAL-COMMUNICATIVE APPROACH - Oybekova Gulnoza Oybek qizi (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA’LIMNING INNOVATSION YO’NALISHLARI, 2025)
This scientific article investigates pedagogical foundations and methodological strategies for enhancing translation competence among prospective foreign language teachers, with a particular focus on undergraduate English majors in Uzbekistan. The study examines translation not merely as a linguistic exercise but as a multi-dimensional process involving intercultural awareness, functional literacy, and strategic mediation. Drawing upon cognitive, communicative, and functionalist translation theories, as well as local pedagogical practice, this research offers a comprehensive model integrating traditional approaches with modern educational technologies. The implications for teacher education curriculum development and translational didactics are discussed.